Manejo complejo del hematoma intramural de aorta descendente: a propósito de un caso - Torres-Restrepo, Juan Manuel (2020)
Acute aortic syndromes (AAS) include a variety of overlapping anatomical and clinical conditions. Intramural hematoma (IMH), penetrating aortic ulcer (UAP), and aortic dissection occur in isolation or may coexist in the same patient. All entities are potentially life threatening, so prompt diagnosis and management are a primary goal of care. IMH represents 5-30% of all AAS and 60-70% of cases are located in the descending portion of the aorta. The diagnosis relies on a high index of clinical suspicion and on the use of complementary images (computed tomography and magnetic resonance imaging). Management is conservative, but patients with persistent pain despite treatment, with hemodynamic instability, with a maximum diameter of the aorta of> 55 mm, with periaortic hemorrhage and focal intimal disruptions have a higher risk of mortality in the acute phase, therefore surgical management should be considered initially endovascular. We present the case of a 69-year-old patient, in whom IMH was diagnosed in the course of a hypertensive emergency and who required hybrid management due to high-risk anatomical characteristics with only endovascular management.